Effects of grass species and grass growth on atmospheric nitrogen deposition to a bog ecosystem surrounded by intensive agricultural land use. Issue 13 (3rd June 2015) - Hurkuck, Miriam; Brümmer, Christian; Mohr, Karsten; Spott, Oliver; Well, Reinhard; Flessa, Heinz; Kutsch, Werner L.
Abstract We applied a 15N dilution technique called "Integrated Total Nitrogen Input" (ITNI) to quantify annual atmospheric N input into a peatland surrounded by intensive agricultural practices over a 2‐year period. Grass species and grass growth effects on atmospheric N deposition were investigated using Lolium multiflorum and Eriophorum vaginatum and different levels of added N resulting in increased biomass production. Plant biomass production was positively correlated with atmospheric N uptake (up to 102.7 mg N pot−1) when using Lolium multiflorum. In contrast, atmospheric N deposition to Eriophorum vaginatum did not show a clear dependency to produced biomass and ranged from 81.9 to 138.2 mg N pot−1. Both species revealed a relationship between atmospheric N input and total biomass N contents. Airborne N deposition varied from about 24 to 55 kg N ha−1 yr−1. Partitioning of airborne N within the monitor system differed such that most of the deposited N was found in roots of Eriophorum vaginatum while the highest share was allocated in aboveground biomass of Lolium multiflorum. Compared to other approaches determining atmospheric N deposition, ITNI showed highest airborne N input and an up to fivefold exceedance of the ecosystem‐specific critical load of 5–10 kg N ha−1 yr−1.